Strategi Pengurangan Ketimpangan Pendapatan di Jawa Barat Melalui Peningkatan Pendidikan dan Pengurangan Kemiskinan - Abdul Rahman (Universitas Veteran Bangun Nusantara, 2025)
Income inequality remains a major challenge in the economic development of West Java Province, despite positive economic growth in recent years. This study aims to analyze the effects of economic growth, education level, and poverty rate on income inequality slot maxwin across 27 regencies/cities in West Java during the 2019–2023 period. The method employed is panel data regression using 135 observations, analyzed through the Fixed Effect Model (FEM) based on the results of Chow and Hausman tests. The findings reveal that economic growth does not have a significant effect on income inequality. In contrast, education level and poverty rate are found to significantly influence income inequality. These results underscore the importance of enhancing education quality and reducing poverty as strategic efforts to mitigate income disparities. The study also indicates that non-inclusive economic growth alone is insufficient to reduce income inequality. Policy implications point to the need for improving access to education and implementing empowerment programs for the poor. This study is limited by the scope of variables and the relatively short time frame, suggesting the need for future research using a more comprehensive and extended approach